Determinants of User Satisfaction in Mobile Commerce: UTAUT 2 model - Julija Vidosavljević; Veljko Marinković; Dražen Marić (Anali Ekonomskog fakulteta u Subotici, 2025)
According to growing trends, there is an evolution of models that explain consumer behavior in the domain of accepting new technologies. The UTAUT model stands out as one of the most commonly used models, which was created as a result of the integration of many that preceded it. The aim of the study is to determine whether variables – performance expectancy, effort expectancy, social influence, facilitating conditions, price value, hedonic motivation, and habit - influence user satisfaction in mobile commerce. The sample consists of 210 respondents. The study applied descriptive statistical analysis, reliability analysis, correlation analysis, and multiple regression analysis. The results show that variables such as performance expectancy, facilitating conditions, hedonic motivation, price value, and habit are determinants of user satisfaction with mobile commerce services. The research findings can be beneficial for mobile commerce service providers in terms of creating loyalty programs, providing added value, and creating an overall consumer experience that is appealing to customers. Given that previous research, especially in the domestic literature, was focused on some of the earlier established models such as TAM or UTAUT, the originality of this paper lies in the use of the contemporary UTAUT2 model.